Forming Islamic Character through the Implementation of the Art of Reading the Qur'an in Islam - Samuji, Samuji (STAI MA'ARIF MAGETAN, INDONESIA, 2024)
Islamic character is a character that needs to be developed by educators and this character needs to be possessed by students in Islamic education. Through the application of the art of reading the Qur'an, it is hoped that it will be able to provide knowledge and understanding for students about the importance of Islamic character, thereby making students become people who love and enjoy reading the Qur'an. Starting from this study, this scientific work aims to describe how the art of reading the Qur'an is implemented in the formation of students' Islamic character. This type of research is a type of library research. Data collection techniques use library techniques (Librerary Research). Meanwhile, for analytical techniques, the author uses data reduction and data presentation and drawing conclusions. The conclusion of this scientific work is that the formation of Islamic character can be formed through the implementation of the art of reading the Koran.